Surgeon’s dilemma: should I save patient’s life at any cost? - Kocańda, Kamila; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2017)
Every doctor practicing treatment in the field of medicine may be confronted with a serious question: should I save my patient’s life at any cost? If a doctor resigns from emergency procedures, he/she will risk the patient’s death. However, if he/she decides to proceed regardless of a Jehovah’s Witness patient’s statement of will, in which he or she refuses transfusion, he/she takes a risk of illegal medical intervention. There is neither an easy answer, nor a serious solution, thus the only way is to choose the lesser of two evils. Notwithstanding legal issues, there are still ethical problems, which result in an internal dilemma for a doctor.